FORMAT PEMBELAJARAN PILIHAN GURU UNTUK ANAK KEMBALI SEKOLAH SELAMA PANDEMI COVID-19 - Ali Audah (PREMIERE : Journal of Islamic Elementary Education, 2020)
In the midst of the Covid-19 pandemic, there is a need to understand teacher choices for the format of teaching children at the start of the 2020-2021 academic year. The aim of the study was to assess teacher choices in school versus virtual at home learning during the 2019–2020 school year and the factorsassociated with the choice. Participants were 100 samples of teachers on elementary, junior and high school in the City of Jombang. Teachers are asked to fill out an online survey about initial options for students to return to the school learning environment. The results showed that teachers on the junior and high school are more supportive of the choice of the hybrid learning format in schools and the scheduled virtual hybrid teaching and do not support the choice of face-to-face traditional learning formats in schools. Meanwhile, elementary school teachers are more supportive of traditional learning formats. Regardless of school level, concerns about child health and safety were the factors most strongly correlated with teacher preferences for in-school learning versus virtual learning at home. This data highlights the importance of plans to reopen schools that offer virtual choices and address teacher concerns about child health and safety amid the Covid-19 pandemic.